Kelantan Peranakan Chinese language and marker of group identity - Pue, Giok Hun; Ong, Puay Liu; Loo, Hong Chuang (Penerbit Universiti Kebangsaan Malaysia, 2019)
Although the status of the national language of Malaysia has been consolidated in the Constitution, the Malay language remains commonly associated with a specific segment of Malaysian society, i.e., the Malays. The language is often seen as a distinct marker for Malayness whereas the non-Malay ethnic groups, particularly in Peninsular Malaysia, are not widely associated with the language. The Chinese as the largest minority ethnic group in the Peninsular, are often stereotypically depicted as relatively less fluent or knowledgeable in Malay language, at times not beyond the colloquial ‘bahasa pasar’. Such a scenario suggests that language-wise, Malaysian society remains divided along ethnic lines. This paper seeks to highlight Malay language use among Peranakan Chinese youth in Kelantan. While their higher level of Malay language proficiency vis-à-vis mainstream Chinese is readily acknowledged, findings from content analyses of qualitative data collected in a focus group discussion also suggest that such proficiency in Malay language is achieved due to it being pivotal to the continuity of their identity as both Kelantan Peranakan Chinese and Kelantanese. In short, the Kelantan Peranakan Chinese community is a good example that proficiency in Malay language as national language can exist in tandem with the group’s mother tongue language, and thus should be celebrated and supported towards building a common identity as part of nation-building in Malaysia.